2014
DOI: 10.1002/cmdc.201402459
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Mono‐ and Disubstituted 1H‐Pyrazolo[3,4]pyrimidines and 9H‐Purines as Catalytic Inhibitors of Human DNA Topoisomerase IIα

Abstract: Human DNA topoisomerase IIα (htIIα) is a validated target for the development of anticancer agents. Based on structural data regarding the binding mode of AMP-PNP (5'-adenylyl-β,γ-imidodiphosphate) to htIIα, we designed a two-stage virtual screening campaign that combines structure-based pharmacophores and molecular docking. In the first stage, we identified several monosubstituted 9H-purine compounds and a novel class of 1H-pyrazolo[3,4]pyrimidines as inhibitors of htIIα. In the second stage, disubstituted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 64 publications
(320 reference statements)
1
31
0
Order By: Relevance
“…In our recent studies we focused on compounds that target the htIIα ATP binding site and successfully evaluated several chemical classes of inhibitors; 4‐aminotriazines ( 2‐3 ), triazin‐2‐ones (4‐ 5 ), as well as purines and pyrazolopyrimidines ( 6 ‐ 10 ) . Our present study represents a continuation of our ongoing efforts in the field of htIIα inhibitors.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In our recent studies we focused on compounds that target the htIIα ATP binding site and successfully evaluated several chemical classes of inhibitors; 4‐aminotriazines ( 2‐3 ), triazin‐2‐ones (4‐ 5 ), as well as purines and pyrazolopyrimidines ( 6 ‐ 10 ) . Our present study represents a continuation of our ongoing efforts in the field of htIIα inhibitors.…”
Section: Introductionmentioning
confidence: 92%
“…Our present study represents a continuation of our ongoing efforts in the field of htIIα inhibitors. We used our previously discovered pyrazolopyrimidine and purine‐based compounds ( 6 ‐ 10 ) as a starting point for the ligand‐based drug design in an attempt to improve the potency, as well as to probe for a novel chemical class and thus expand the chemical space of htIIα catalytic inhibitors that target the ATP binding site.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4tetra hydropyrimidine analogue was found to be potent against various human cancer cell lines (Bari et al, 2015). Triazolo-pyrimidinone (Mohamed et al, 2015b) and pyrazolo-pyrimidine (Pogorelcnik et al, 2015) with the structures shown in Fig. 40, revealed promising anticancer activities compared to the activity of the commonly used anticancer drug, doxorubicin in both MCF-7 and A549 cell lines.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Drugs which affect DNA biosynthesis have received much attention and amongst them pyrimidine derivatives remain the most important (Cieplik, 1992;Pogorelcnik et al, 2015). Many pyrimidine incorporating compounds constitute an assortment of drugs with ability to hinder biosynthesis of pyrimidine nucleotides or act effectively as naturalist metabolites, thus interfering in substantial ellular processes, for example nucleic acids synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesized glycosides and their derived analogs (Zhao et al, 2008;Zhao and Li, 2007) revealed considerable inhibitory activity of DNA-topoisomerase II (TopoII) that controls DNA topology by transitory cleavage of the DNA double helix, which was affirmed as important molecular target of anticancer drugs (Champoux, 2001;Pommier et al, 2010). Moreover, studied biological assays found that exotic sugar part confers a number of glycosides with best conformation possessing high binding affinities via hydrogen bonding to the entry of the ATPase pocket (Gui et al, 2011;Shi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%